People, places, and time: a large-scale, longitudinal study of transformed avatars and environmental context in group interaction in the metaverse. Issue 2 (6th January 2023) - Han, Eugy; Miller, Mark R; DeVeaux, Cyan; Jun, Hanseul; Nowak, Kristine L; Hancock, Jeffrey T; Ram, Nilam; Bailenson, Jeremy N
Abstract: As the metaverse expands, understanding how people use virtual reality to learn and connect is increasingly important. We used the Transformed Social Interaction paradigm (Bailenson et al., 2004 ) to examine different avatar identities and environments over time. In Study 1 ( n  =   81), entitativity, presence, enjoyment, and realism increased over 8 weeks. Avatars that resembled participants increased synchrony, similarities in moment-to-moment nonverbal behaviors between participants. Moreover, self-avatars increased self-presence and realism, but decreased enjoyment, compared to uniform avatars. In Study 2 ( n  =   137), participants cycled through 192 unique virtual environments. As visible space increased, so did nonverbal synchrony, perceived restorativeness, entitativity, pleasure, arousal, self- and spatial presence, enjoyment, and realism. Outdoor environments increased perceived restorativeness and enjoyment more than indoor environments. Self-presence and realism increased over time in both studies. We discuss implications of avatar appearance and environmental context on social behavior in classroom contexts over time. Lay Summary: Understanding how people connect socially via avatars in immersive virtual reality has become increasingly important given the prolific rise of the metaverse. In two large-scale, longitudinal field experiments, we extended predictions of the Transformed Social Interaction paradigm to investigate how the appearance of avatars and the characteristics of the virtual environment influenced people's behaviors and attitudes over time. In Study 1, we demonstrated the effects of time: group cohesion, presence, enjoyment, and realism measures increased over time, and the effects of appearance: When represented by avatars that looked like themselves, people displayed more synchronous nonverbal behaviors, or were more "in sync" with others, and reported the image quality of the environment and people as more realistic. On the other hand, when people wore the same uniform avatar, they experienced more enjoyment. In Study 2, we demonstrated the effects of the environment: When in more spacious virtual environments, there was more synchronous movement and people reported feeling greater restoration, group cohesion, pleasure, arousal, presence, enjoyment, and realism, than in constrained environments. When in outdoor environments with elements of nature, people reported feeling greater restoration and enjoyment than in indoor environments.